Safeguarding the polar regions from dangerous geoengineering: a critical assessment of proposed concepts and future prospects - Siegert, Martin; Sevestre, Heïdi; Bentley, Michael J.; Brigham-Grette, Julie; Burgess, Henry; Buzzard, Sammie; Cavitte, Marie; Chown, Steven L.; Colleoni, Florence; DeConto, Robert M.; Fricker, Helen Amanda; Gasson, Edward; et al. (Frontiers in Science, 2025)
Fossil-fuel burning is heating the planet with catastrophic consequences for its habitability and for the natural world on which our existence depends. Halting global warming requires rapid and deep decarbonization to “net zero” carbon dioxide (CO2) emissions, which needs to be achieved by 2050 if warming is to remain within the limits set out by the 2015 Paris Agreement. However, some scientists and engineers claim that a mid-century decarbonization target will not be reached, and they propose that we should focus on technological geoengineering “fixes” or “climate interventions” that could delay or mask some of the impacts of global warming. They often cite the need to slow warming in polar regions because they are experiencing rates of warming higher than the global average, with severe and irreversible projected consequences both locally (e.g., on fragile ecosystems) and globally (e.g., on sea level). Several geoengineering concepts exist for polar regions, but they have not been fully examined by the polar science community, nor integrated with an understanding of polar dynamics and responses. Here, we evaluate five of those polar geoengineering concepts and highlight the significant issues and risks relating to technological availability, logistical feasibility, cost, predictable adverse consequences, environmental damage, scalability (in space and time), governance, and ethics. According to our expert assessment, none of these geoengineering ideas pass scrutiny regarding their use in the coming decades. Instead, we find that the proposed concepts would be environmentally dangerous. It is clear to us that the assessed approaches are not feasible, and that further research into these techniques would not be an effective use of limited time and resources. It is vital that these ideas do not distract from the priority to reduce greenhouse gas (GHG) emissions or from the critical need to conduct fundamental research in the polar regions.